Size effect in concrete blocks under local pressure - Ince, R; Arici, E (Techno-Press, 2005)
Numerous tests on concrete structure members under local pressure demonstrated that the compressive strength of concrete at the loaded surface is increased by the confinement effect provided by the enveloping concrete. Even though most design codes propose specific criteria for preventing bearing failure, they do not take into consideration size effect which is an important phenomenon in the fracture mechanics of concrete/reinforced concrete. In this paper, six series of square prism concrete blocks with three different depths (size range = 1:4) and two different height/depth ratios of 2 and 3 are tested under concentrated load. Ultimate loads obtained from the test results are analysed by means of the modified size effect law (MSEL). Then, a prediction formula, which considers effect of both depth and height on size effect, is proposed. The developed formula is compared with experimental data existing in the literature. It is concluded that the observed size effect is in good agreement with the MSEL.
Keywords: concrete; bearing strength; size effect law; modified size effect law